A method of recording condylar movements and joint sounds - Hannan Patrick J.; West Victor C.; Faulkner Keith D.B (Sciendo, 1989)
A commercial tracking system has been adapted within the University of Melbourne, which is designed to track the movement of infra-red light emitting diodes, (LEDs). The movement of the diodes was recorded by photosensimetric recording devices, and sent to a data recorder, then to a differential amplifier, and the signal stored on magnetic tape, or viewed on a cathode ray oscilloscope, or plotted on a chart plotter or an X-Y plotter. The equipment was used to track the movement of LEDs, which were secured to a Iower arch face bow, which was in tum secured to the teeth via a universal joint, and an acrylic clutch.